2006
DOI: 10.1002/aqc.781
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the sampling scale on zooplankton community assessment and its implications for the conservation of temporary ponds in south‐west Spain

Abstract: ABSTRACT1. The zooplankton (rotifer and microcrustacean) assemblages of temporary ponds in the Don˜ana National Park (south-west Spain) have been compared in two surveys of contrasting scales that resulted in the same number of samples: an extensive survey of 36 ponds sampled in May 1998 (or widespread survey) and a survey of nine ponds sampled four times over 2 years (or cumulative survey).2. The total number of microcrustacean and rotifer taxa was larger in the cumulative survey (43 and 41 taxa, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…3). Fahd et al (2007) reported that increasing within-year sampling yielded higher species diversity than sampling additional systems within the same region, a result consistent with our observations. A key compositional difference between 1976 and 1997 was a shift away from dominance by species including Keratella cochlearis, Collotheca mutabilis, and Synchaeta kitina and increased dominance by K. quadrata, Trichocerca similis, Conochilus unicornis, Pompholyx sulcata, and Polyarthra spp.…”
Section: Rotifer Community Analysessupporting
confidence: 92%
“…3). Fahd et al (2007) reported that increasing within-year sampling yielded higher species diversity than sampling additional systems within the same region, a result consistent with our observations. A key compositional difference between 1976 and 1997 was a shift away from dominance by species including Keratella cochlearis, Collotheca mutabilis, and Synchaeta kitina and increased dominance by K. quadrata, Trichocerca similis, Conochilus unicornis, Pompholyx sulcata, and Polyarthra spp.…”
Section: Rotifer Community Analysessupporting
confidence: 92%
“…Arnott et al, 1998;Fahd et al, 2007). Ideally samples should be taken more than one month a year, but comparison at several points in the annual cycle is difficult in temporary ponds with variable hydroperiods.…”
Section: Discussionmentioning
confidence: 99%
“…Macroinvertebrates which are well adapted to temporary ponds adopt different physiological and behavioral mechanisms to survive desiccation (Williams 2006), with dispersal into permanent ponds being the most common strategy followed by dormant life-history stages such as resistant eggs, larvae and adults burying into the mud (Wiggins et al 1980;Higgins and Merrit 1999;Bilton et al 2001). Dispersal also is favored by physical links between sites which can occur following heavy rainfall (Fahd et al 2007). As high connectivity is one of the main drivers of nestedness in biological communities (Boecklen 1997;Cook and Quinn 1995;Wright et al 1998;Higgins et al 2006) and dispersal has been suggested as being important in driving nested patterns (Patterson 1990;Atmar and Patterson 1993;Loo et al 2002;Hausdorf and Hennig 2003), we expected, and found, good dispersers to be more highly nested than poor and non-dispersing taxa (Cook and Quinn 1995).…”
Section: Monthly Variation In Species Richness and Nestednessmentioning
confidence: 97%